Optical solitons with resonant nonlinear Schrodinger's equation using three integration schemes - Tchier, F.; Kilic, B.; İnç, Mustafa; Ekici, M.; Sonmezoglu, A.; Mirzazadeh, M.; Belic, M. (Natl Inst Optoelectronics, 2016)
This paper integrates resonant nonlinear Schrodinger equation (RNLSE) with power law nonlinearity and time dependent coefficients. The first integral method (FIM) is applied to reach the optical solitons of RNLSE with power law nonlinearity and time dependent coefficients which are the terms of velocity dispersion, linear and nonlinear terms and also resonant one.
Keywords: First integral method; Generalized Kudryashov's approach; Extended trial scheme approach; Soliton